The relationship between parental alcohol drinking habits and children’s self-esteem: An Icelandic youth sample - Erla Rut Eggertsdóttir 1994- (2018)
Alcoholism is a quite common problem worldwide that has made a great impact on families for a long time. Parental support and sensitive care are among few things that can affect children’s self-esteem and alcoholic parents often fail to provide this support and as a result it can have a negative effect on the child’s self-esteem. This study explored the relationship between parental drinking and the self-esteem among children and if parental alcohol drinking affected the children’s self-esteem equally. The participants in the study were in total 7514 adolescents in 9th and 10th grade in Iceland. The survey took place in 2009 and focused on various aspects of health and well being, including parental drinking and self-esteem. Results showed that the mothers’ and the fathers’ alcohol drinking negatively related to the participants self-esteem. There was a significant interaction effect showing that the frequency of parental drinking had a negative relationship with the participants’ self-esteem, with the lowest self-esteem observed among those who had a mother that drank alcohol occasionally or often and a father who drank alcohol occasionally or often. The results also showed that parental alcohol drinking had the same effects on the self-esteem of both genders. Key words: alcoholism, parental alcoholism, families of alcoholics, self-esteem, children's self-esteem, Rosenberg self-esteem scale, gender differences Alkóhólismi er tiltölulega algegnt vandamál á heimsvísu og hefur haft margvísleg áhrif á fjölskyldur í gegnum tíðina. Stuðningur foreldra og náin tengsl á milli foreldra og barna eru þættir sem geta haft áhrif á sjálfsálit barna. Foreldrum með drykkjuvanda mistekst oftar en ekki að veita barninu sínu þennan stuðning og nánu tengsl sem getur í kjölfarið haft neikvæðar afleiðingar fyrir sjálfsálit barnsins. Þessi rannsókn kannaði sambandið á milli áfengis drykkju foreldra og sjálfsálits barnanna en einnig hvort að áfengis drykkja foreldra hefði sömu áhrif á sjálfsálit kynja. Þátttakendurnir í þessari ...